The wishing stone - Pike, Christopher, 1955-; Copyright Paperback Collection (Library of Congress) (New York : Pocket Books, 1996)
When Adam and his friends find a cube-shaped crystal while hiking, they find it makes their wishes come true. Unfortunately, the stone wants to be paid for what it gives.
"A Minstrel book."
Keywords: Wishes -- Fiction; Horror tales; Children's stories; Ghost stories